The Grammatical permissibility of the Letter “L” from Surat Al-Rum to Surat Al-Jathia - Aziz Ay, Muhammad Hussein; Ahmed Al Bayati, Abdul Karim Abd (Journal of Tikrit University for Humanities, 2023)
The phenomenon of grammatical permissibility is not a new born one, it rather appeared alongside grammar appearance. The effect of this phenomenon is clearly recognized in Arabic language in a sense that speech is no more a one-sided meaning, but rather has gone towards other aspects that are appropriate to the context and the intention of the speaker. The researcher reflects on this notion and how one needs to meditate the meaning especially when he finds himself in front of rigid structure with multiple connotations. As such, the context must be taken closer. This research tackles the concept of permissibility as a term, its origin, its importance, and brings examples of words that represent the phenomenon of permissibility.